Public Perception on the Implementation of PON XXI Event North Sumatera-Aceh at Situngkir Panguruan Beach in 2024 - Zuhriyah, Zuhriyah; Zarei, Azadeh; Gula , Louie Peter; Siregar, Samsuddin (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2025)
The purpose of the study. This study aimed to evaluate public perception regarding the implementation of PON XXI Event North Sumatra-Aceh at Situngkir Panguruan Beach in 2024, focusing on economic impact, infrastructure development, environmental considerations, and cultural integration. The research examined community attitudes toward event implementation and its implications for local development. Materials and methods. A cross-sectional descriptive study was conducted using a structured questionnaire administered to 100 residents of Situngkir Village, selected through stratified random sampling. Data collection employed a 45-item questionnaire covering five dimensions, utilizing a 5-point Likert scale. Analysis included descriptive statistics, factor analysis, and multiple regression analysis using SPSS version 26.0. Results. The study revealed predominantly positive perceptions of PON XXI Event implementation, with 82.5% reporting positive business opportunity expectations and 95% satisfaction with infrastructure development. Multiple regression analysis identified economic benefits (β = 0.445, p < 0.001), infrastructure development (β = 0.376, p < 0.001), and environmental management (β = 0.315, p = 0.002) as significant predictors of overall satisfaction. The model explained 78.4% of variance in community satisfaction (adjusted R² = 0.784, p < 0.001). Conclusions. The implementation of PON XXI Event at Situngkir Panguruan Beach demonstrated successful integration of event requirements with community needs, particularly in economic opportunities and infrastructure development. However, environmental management requires additional attention, particularly in waste management and beach conservation. The findings provide valuable insights for future sport-tourism event planning and regional development strategies.